Normative Legal Research in Indonesia: Its Originis and Approaches - Tunggul Ansari Setia Negara (Audito Comparative Law Journal (ACLJ), 2023)
The legal research method is one of the academic fields that continues to generate debate among law students and law colleges in Indonesia. This debate is important because the research method is a means for a legal scholar to obtain the truth. This article maps the debate on normative and socio-legal research, emphasizing the former type of research. This article explores the origins and debates of normative legal research methods in Indonesian legal education and some of the mainstream approaches commonly used in normative legal studies. This condition does not aim to develop a claim on the validity of normative legal research methods as the only research method but rather to position normative legal research proportionally in the legal scholarship in Indonesia.